Development of barley and yeast β-glucan aerogels for drug delivery by supercritical fluids. (December 2017) - Salgado, Marta; Santos, Filipa; Rodríguez-Rojo, Soraya; Reis, Rui L.; Duarte, Ana Rita C.; Cocero, María José
Graphical abstract: Highlights: Barley and yeast β-glucan aerogels were processed by supercritical CO2 drying. More elastic and stable hydrogel with yeast β-glucan (YBG) due to chain conformation. Thicker and more resistant aerogel with YBG and with higher concentration. Up to 15% loading of acetylsalicylic acid by impregnation with supercritical CO2 . Release controlled by swelling and diffusion of the polymer, with lag time in BBG. Abstract: Polysaccharide aerogels are a good alternative as carriers for drug delivery, since they allow high loading of the active compounds in matrices that are non-toxic, biocompatible and from a renewable feedstock. In this work, barley and yeast β-glucans aerogels were produced by gelation in aqueous solution, followed by solvent exchange and drying with supercritical CO2 . First, viscoelastic properties and melting profile of the hydrogels were determined. Then, the obtained aerogels were analyzed regarding morphology, mechanical properties and behavior in physiological fluid. Both in the hydrogels and in the aerogels, big differences were observed between barley and yeast β-glucans due to their different chain structure and gelation behavior. Finally, impregnation of acetylsalicylic acid was performed at the same time as the drying of the alcogels with supercritical CO2 . The release profile of the drug in PBS was analyzed in order to determine the mechanism governing the release from the β-glucan matrix.